The Roles of Organizational Politics and Procedural Fairness in the Relationship between Performance Evaluation Systems and Budget Gaming Behavior - SeTin SeTin; Roy Sembel; Yvonne Augustine Sudibyo; Ari Purwanti (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
This study investigates the relationship between performance evaluation systems and budget gaming behavior. Specifically, it examines the mediating role of organizational politics and procedural fairness. Data collection was conducted by a questionnaire survey of managers of go-public manufacturing companies in Indonesia. Based on a sample of 128 responses, the partial least squares results indicate that general political behavior, the politics of pay and promotion policies, and procedural fairness significantly mediate the non-financial measures and budget gaming relationship. In contrast, the results indicate that the mediating effects of organizational politics and procedural fairness on the relationship between relative performance measures and budget gaming behavior are generally insignificant. This study supports the goal setting theory and the organizational justice theory, and contributes to the management control system literature by recognizing the importance of performance evaluation systems, the importance of understanding political behavior and the perception of fairness to overcome budget gaming behavior. This study provides assurance that organizations can reduce budget gaming behavior through using non-financial measures or incentives.